Socialising tourism after COVID-19: reclaiming tourism as a social force? - Freya Higgins-Desbiolles; Bobbie Chew Bigby; Adam Doering (Journal of Tourism Futures, 2022)
Purpose – This article considers the possibilities of and barriers to socialising tourism after the coronavirus disease 2019 (COVID-19) pandemic. Such an approach allows us to transform tourism and thereby evolve it to be of wider benefit and less damaging to societies and ecologies than has been the case under the corporatised model of tourism. Design/methodology/approach – This conceptual analysis draws on the theorisation of “tourism as a social force” and the new concept of “socialising tourism”. Using critical tourism approaches, it seeks to identify the dynamics that are evident in order to assess the possibilities for socialising tourism for social and ecological justice. It employs an Indigenous perspective that the past, present and future are interconnected in its consideration of tourism futures. Findings – COVID-19 has fundamentally disrupted tourism, travel and affiliated industries. In dealing with the crisis, borders have been shut, lockdowns imposed and international tourism curtailed. The pandemic foregrounded the renewal of social bonds and social capacities as governments acted to prevent economic and social devastation. This disruption of normality has inspired some to envision radical transformations in tourism to address the injustices and unsustainability of tourism. Others remain sceptical of the likelihood of transformation. Indeed, phenomena such as vaccine privilege and vaccine tourism are indicators that transformations must be enabled. The authors look to New Zealand examples as hopeful indications of the ways in which tourism might be transformed for social and ecological justice. Practical implications – This conceptualisation could guide the industry to better stakeholder relations and sustainability. Social implications – Socialising tourism offers a fruitful pathway to rethinking tourism through a reorientation of the social relations it fosters and thereby transforming its social impacts for the better. Originality/value – This work engages with the novel concept of “socialising tourism”. In connecting this new theory to the older theory of “tourism as a social force”, this paper considers how COVID-19 has offered a possible transformative moment to enable more just and sustainable tourism futures.